The Effect of Repetitive Transcranial Magnetic Stimulation on Motor Symptoms in Hereditary Spastic Paraplegia. (12th May 2019) - Antczak, J.; Pera, J.; Dąbroś, M.; Koźmiński, W.; Czyżycki, M.; Wężyk, K.; Dwojak, M.; Banach, M.; Slowik, A.
Abstract : Background . Hereditary spastic paraplegia (HSP) is a heterogeneous group of inherited disorders affecting predominantly the motor cortex and pyramidal tract, which results in slowly progressing gait disorders, as well as spasticity and weakness of lower extremities. Repetitive transcranial magnetic stimulation (rTMS) has been previously investigated as a therapeutic tool for similar motor deficits in a number of neurologic conditions. The aim of this randomized, controlled trial was to investigate the therapeutic potential of rTMS in various forms of HSP, including pure and complicated forms, as well as adrenomyeloneuropathy. Methods . We recruited 15 patients (five women and 10 men; mean age43.7 ± 10.6 years) with the mentioned forms of HSP. The intervention included five sessions of bilateral 10 Hz rTMS over primary motor areas of the muscles of lower extremities and five sessions of similar sham stimulation. Results . One patient dropped out due to seizure, and 14 patients completed the study protocol. After real stimulation, the strength of the proximal and distal muscles of lower extremities increased, and the spasticity of the proximal muscles decreased. Change in spasticity was still present during follow-up assessment. No effect was observed regarding gait velocity. No changes were seen after sham stimulation. A post hoc analysis revealed an inverse relation between motor threshold and the change of the strength after active rTMS. Conclusions . rTMS may have potential in improving weakness and spasticity of lower extremities in HSP, especially of proximal muscles whose motor areas are located more superficially. This trial is registered with Clinicaltrials.govNCT03627416 .